Isolated spin polarized hydrogen atoms as targets for laser-induced polarized electron acceleration - Dimitris Sofikitis; Marios G. Stamatakis; Dimitrios G. Papazoglou; Dimitrios G. Papazoglou; T. Peter Rakitzis; T. Peter Rakitzis (Frontiers in Physics)
High density Spin Polarized Hydrogen (SPH) atoms, which can be prepared using UV dissociation of hydro-halide molecules, can be attractive as potential targets for laser ionization/acceleration schemes aiming to create high energy and high current polarized electron beams. However, for these SPH targets to be of practical use, they have to be spatially isolated from the halide atoms which accompany hydrogen in the parent hydro-halide molecule. We show how the UV dissociation dynamics of hydro-halides and the dissociation geometry and timing can be combined to prepare a variety of isolated SPH targets aimed to accommodate laser acceleration schemes.